Tumpang Tindih: Sebuah Komposisi Musik Dalam Interpretasi Personal - Warsana - (Institut Seni Indonesia Yogyakarta, 2012)
Komposisi musik ini merupakan bagian dari relfeksi pengalaman masa kecil penulis ketika harus menghafalhuruf Jawa Hanacaraka. Sebagai rangsang awal dalam karya ini adalah ide dari legenda Ajisaka tentang menciptakanhuruf Jawa Hanacaraka. Ketidakpastian dalam satu keputusan memunculkan keputusan baru adalah gambaran tatanan kehidupan dewasa ini oleh karena bahasa serta sikap dalam mengambil tindakan yang tumpang tindih. Dalam komposisi ini Hanacaraka yang terdiri dari 20 kata diaktualisasikan ke dalam beberapa instrumen musik dan sumber bunyi dengan karakter yang berbeda. Komposisi ini memadukan instrumen gong, bonang, pralon, othokothok, klonthongan sapi, serta pengolahan huruf Jawa Hanacaraka. Komposisi ini memperhatikan tiga elemen musik yakni ritme, melodi, dan harmoni dengan pola permainan sukat yang berbeda. Penyajian komposisi sebagai sebuah pertunjukan dapat dinikmati secara audio maupun visual. Oleh karena itu, diperlukan penggarapan baik penyajian musikal maupun non musikal. Dengan mengacu pada pertunjukan teater maka diperlukan stage, agar terjadi komunikasi antara penonton dengan pemain dalam satu arah pandang mata.Kata kunci: tumpang tindih, hanacarakaABSTRACTThe Tumpang Tindih: A Music Composition. Observing the current reality of twisted, overlap, and unstructured life becomes the theme of this composition. Music composition entitled “Overlapping” represents the part of the writer’srefl ective experience on his childhood when he must memorize Javanese letters of Hanacaraka. The diffi culty in learningand memorizing the Javanese letters becomes the basic idea of the birth of his composition. The Legend of Ajisaka aboutcreating the Javanese letters of Hanacaraka becomes the stimulus of an early idea in this composition. The uncertainty inone decision which emerges another new decision is a description of life arrangement nowadays because of the overlapping of the language and attitude. In this composition, Hanacaraka with 20 letters is actualized into some musical instruments and sound with different characters. This composition combines the gong instrument, bonang, “pralon”- hard pipe, othokothok – a traditional children’s toy, “klontongan sapi”- the bell horn by the ox, and also the Javanese letters of Hanacaraka arrangement. All the sound mentioned above; then is composed into three music elements, namely the existence of rhythm, melody, and harmony with different “sukat”- measure such as 3/4, 4/4, 5/4, 7/4. This composition is presented as a performance, which can be appreciated through audio and visual. Therefore, a good musical and non- musical arrangement is necessarily used. Referring to the theatre performance, hence a stage is needed in order to be a direct communication media for the audience and players.Keywords: overlapping, hanacaraka